CZECH CIVIL AIRPLANES MANUFACTURES AND THEIR POTENTIAL ON EMERGING MARKETS TYPE OF CHINA - Brix, Vojtěch; Frömmel, Tomáš; Prokop, Jaromír; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2017)
In this thesis the author analyses the potential of aircraft manufacturing industry of the Czech Republic on emerging markets. Czech manufacturers have been operating only in two of the main sub-segments of the whole industry. Three main manufacturers were selected based on their revenues and each analysed from the financial, product portfolio, sales, and R&D point of view. The markets were selected applying the rating approach. For the purposes of the selection process a multi-criterial matrix was constructed of eleven parameters and two specific superstructures for each of the segments within the range. In the last part, the economic impact on the Czech Republic was estimated, specifically in terms of the labour market and contribution to the state budget via taxes and foreign trade balance.
Vedoucí práce: Tomáš Frömmel
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses